The Effect of Competency and Work Motivation on Employee Satisfaction and Its Implications on Employee Performance in Community Health Centers in Bandung City - Arif Rachman; Uce Karna Suganda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the effect of competence and motivation on job satisfaction and employee performance at the Bandung City Community Health Center. The results show that the competency variable criteria are in the poor to very good range, while the work motivation and job satisfaction variables are in the adequate to very good range. Meanwhile, the overall employee performance variable is in the very good category. Further analysis revealed that competence and motivation have a significant influence on job satisfaction, and job satisfaction has a significant influence on employee performance. Overall, competence, motivation, and job satisfaction account for 59.1% of the influence on employee performance, while the remainder is attributed to other variables not examined in this study.